2017
DOI: 10.21608/epx.2017.16392
|View full text |Cite
|
Sign up to set email alerts
|

Adverse health effects among nurses and clinical pharmacists handling antineoplastic drugs: Adherence to exposure control methods

Abstract: Background: Chronic exposure to antineoplastic drugs (ADs) may result in reproductive, liver, renal, lung, and cardiac toxicity. Moreover, bone marrow suppression, mucosal ulcers, and cancer may develop. In developing countries, adverse health effects owing to occupational exposure to ADs and adherence to safe handling guidelines are not well documented. Aim: This study was conducted to determine the health effect of occupational exposure to ADs and evaluate adherence to control methods. Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Five studies included in this review examined exposure to antineoplastic drugs, mainly safe handling practices, and reported that adherence to control measures was suboptimal. A study conducted in Egypt reported a lack of medical surveillance programs and training, inadequate handling practices, and low usage of personal protective equipment [121]. Two studies conducted in Turkey found that only about 40% of participants used biological safety cabinets and that personal protective equipment was not used consistently [113,123].…”
Section: Chemical Hazardsmentioning
confidence: 99%
“…Five studies included in this review examined exposure to antineoplastic drugs, mainly safe handling practices, and reported that adherence to control measures was suboptimal. A study conducted in Egypt reported a lack of medical surveillance programs and training, inadequate handling practices, and low usage of personal protective equipment [121]. Two studies conducted in Turkey found that only about 40% of participants used biological safety cabinets and that personal protective equipment was not used consistently [113,123].…”
Section: Chemical Hazardsmentioning
confidence: 99%
“…Education and training can raise awareness of hospital personnel on the potential hazards of working with cytostatic agents. Previous research in low-and middle-income countries showed that this could be a reason for non-compliancy with safety guidelines (18)(19)(20)(21)(22)(23). Some extremely high levels of cytostatics were probably caused by spilling and remained on the surfaces by inadequate cleaning or cleaning protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Since engineering controls such as biosafety cabinets are costly, healthcare workers in low-and middle-income countries have to rely more on other measures to control hazard (e.g., personal protective equipment) (17). However, studies on safe handling of cytostatic drugs among healthcare workers in middle-income countries reported insufficient or complete lack of specialized training, inappropriate cleaning procedures and a high variability in awareness of potential hazards and use of personal protective equipment (18)(19)(20)(21)(22)(23). In general, these studies indicate the need for a better implementation of guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…A study performed by Elshaer recorded the effects of APs on exposed nurses. Thirty one percent of exposed nurses presented with infertility and 36.36% recorded oral ulcers 135 . Additionally, white blood cell counts were reduced whereas, there was an increase in creatine levels 135 .…”
Section: Contribution Of Chemotherapeutics To the Sdgsmentioning
confidence: 99%